Taxonomy of starred Agama Laudakia stellio in Syria using morphological Data and 12s rDNA in mitochondrial DNA - Al-Masri, Aroub Mohammed; Al-Shaikh, Banan; Al-Saleh, Ismaeel; Makhoul, Manar (Journal of agricultural, environmental and veterinary sciences, 2023)
Morphological Study of the species Laudakia stellio in Syria (within nine years) shows that there are nine groups, which are characterized by their morphological characteristics such as pholidosis, morphometrics and color, each group in exist in a distinct geographical region. Among these nine groups, two of them had characteristics that are similar to known subspecies. These are Laudakia stellio picea known in northern Jordan and southern Syria in the black lava desert, and the subspecies Laudakia stellio daani known in southern Anatolia, which was found in Aleppo governorate. The rest seven groups distributed throughout Syria, are unique in its pholidosis, morphometrics, and color. As for the molecular study through the sequence of the 12s rDNA gene in mitochondrial DNA (conducted in 2015), it shows the presence of two groups in Syria. The samples of the southern and southeastern region, in addition to the Jabbul sample, were located within one main clade with 6 branches close to each other, and the Jabbul sample was distinguished by its relative distance. The rest of the samples (central and northwestern) were part of another clade that included the comparison samples from southern Turkey and were distributed within 3 branches close to each other. The samples of the Lattakia region were similar to the samples of the Turkish Hatay. The second branch, contains samples from Hama and Tartous, while the third branch includes Turkish samples from Adana, thus the samples of laudakia stellio for which the mt 12S rDNA gene was sequenced were distributed into 9 genotypes within two distinct groups. ‏